Pengaruh Kepuasan Kerja Terhadap Intensi Turnover Dimediasi Oleh Quiet Quitting Pada Karyawan - Wilujeng, Raniah Julyan; Prawitowati, Tjahjani (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This research is titled "Job Satisfaction towards Turnover Intention Mediated by Quiet Quitting of Generation Z Employees in East Java Companies". The main focus of this research is to analyze the relationship between job satisfaction, quiet quitting, and turnover intention among Generation Z employees. Generation Z, known for having unique characteristics and a demand for work-life balance, tends to engage in quiet quitting, which is reducing involvement in work without formally resigning. Through interviews and data analysis, this study found that job satisfaction has a significant negative influence on turnover intention. Furthermore, quiet quitting acts as a mediator that strengthens the relationship between job satisfaction and turnover intention. This research provides insights for companies to understand the dynamics of Generation Z employees and emphasizes the importance of creating a supportive work environment to increase job satisfaction and reduce turnover rates. The results of this study are expected to be a reference for companies in formulating more effective human resource management strategies. Keywords: job satisfaction, turnover intention, quiet quitting, work life balance, dan human resources management